Problems of Formally Employed Women: A Case Study of Bahawalnagar, Pakistan - NAWAZ , Muhammad Atif; AFZAL , Noreen; SHEHZADI , Kiran (Asian Journal of Empirical Research, 2013)
The focus of the study is to highlight the problems of working women in formal sector in Bahawalnagar. Sample of 100 formally employed women are selected from four public sector departments as 20 police women, 40 nurses, 20 school teachers and 20 college lecturers using stratified random sampling. Descriptive analysis is used for highlighting the problems faced by working women in said departments. Results reveal that police women are facing low social status and non-recognition of their jobs. Nurses face unscheduled working hours and low wages and school teachers want higher wages for their work. Unavailability of transport is also a major problem to all formally employed women in our sample.